The Predictive Value of Flow-Mediated Dilation and Carotid Artery Intima-Media Thickness for Occult Coronary Artery Disease - ÖZBEN SADIÇ, BESTE; MUTLU, BÜLENT; TİGEN, MUSTAFA KÜRŞAT (WILEY-BLACKWELL, 2011)
Background: Multidetector row computed tomography (MDCT) is an attractive noninvasive alternative to assess overall coronary artery disease (CAD) burden and may reveal coronary plaques, which may be underestimated by conventional coronary angiography. The aim of this study was to determine whether brachial artery flow-mediated dilation (FMD) and carotid artery intima-media thickness (CIMT) might accurately predict patients with occult coronary plaques whose conventional coronary angiographies revealed normal coronary arteries (NCA). Methods: Thirty-five patients with angiographically NCA were consecutively recruited into the study. They underwent MDCT and were divided into NCA group (18 patients; 8 male; 47 +/- 9 years) and occult CAD group (17 patients; 11 male; 50 +/- 10 years) according to presence of coronary plaque. Nineteen consecutive patients with evident CAD (16 male; 54 +/- 7 years) and 19 healthy subjects (10 male; 50 +/- 6 years) were included as control groups. FMD and CIMT were measured by brachial and carotid artery ultrasonography. Results: Occult CAD group had significantly lower FMD and insignificantly higher CIMT than NCA group whereas they had significantly higher FMD and insignificantly lower CIMT than evident CAD group. NCA group had significantly lower CIMT than evident CAD group. Receiver operating characteristic curve analysis demonstrated FMD < 8% (sensitivity: 94.4%; specificity: 73.0%; PPV: 77.3%; NPV: 93.1%) and CIMT = 0.65 cm (sensitivity: 72.2%; specificity: 62.2%; PPV: 65.0%; NPV: 69.7%) could predict patients with CAD. FMD and CIMT were independent predictors of CAD (P < 0.001; OR: 45.630; 95%CI: 5.38386.983 and P = 0.015; OR: 14.226; 95%CI: 1.666121.467, respectively). Conclusion: FMD and CIMT might predict patients with occult CAD and be helpful in selecting patients for MDCT. (Echocardiography 2011;28:1141-1147)
Keywords: carotid artery intima-media thickness; coronary artery disease; endothelial function; flow-mediated dilation; multidetector row computed tomography; CARDIOVASCULAR RISK-FACTORS; SPIRAL COMPUTED-TOMOGRAPHY; C-REACTIVE PROTEIN; ENDOTHELIAL DYSFUNCTION; BRACHIAL-ARTERY; POSTMENOPAUSAL WOMEN; PROGNOSTIC ROLE; WALL THICKNESS; ATHEROSCLEROSIS; ULTRASOUND